(untitled) (Ameghiniana, 2014)
The Paso Flores Formation at Cañadón de Pancho (southern Neuquén Province, Argentina) is composed of four successive sedimentary facies associations: a) thick, lenticular beds of clast-supported conglomerates and sandstone s deposited in a braided fluvial system, b) Laterally persistent laminated and rippled mudstone and siltstone (lacustrine facies) in which three upward coarsening and thickening sandbodies occur (progradational wave-reworked mouth bars), c) interbedded tabular mudstones and more lenticular sandstones which are interpreted as the deposit of a low-sinuosity meandering fluvial system, and d) lenticular bodies of coarse-grained sandstone and granule conglomerates fonned in a braided fluvial system. The palaeofloristic horizon.Tocated in the lacustrine mudstone, is composed of Corystospennae, Cycadales, Ginkgoales and Coniferales, These fossils indicate a latest Triassic age for the Paso Flores Format ion at Cañadón de Pancho. The studied "lacustrine" flora shows some remarkable differences when compared with the classic "fluvial" floras from other Paso Flores Formation localities.